Arecoline inhibits pineal–testis function in experimentally induced hypothyroid rats. (1st January 2020) - Saha, Indraneel; Chakraborty, Suman Bhusan; Chatterjee, Aniruddha; Pradhan, Debajyoti; Chatterji, Urmi; Maiti, B. R.
Abstract: Arecoline is known to cause endocrine dysfunction. In the current article role of arecoline on pineal–testis activity was investigated in hypothyroid rats induced by propylthiouracil (PTU). PTU treatment caused thyroid dysfunction ultrastructurally with a fall in T3 and T4 levels followed by a rise of thyroid stimulating hormone (TSH) level. Pineal activity was impaired by PTU treatment, as evident from degenerated synaptic ribbons and mitochondria of the pinealocytes with depletion of pineal and serum N -acetyl serotonin and melatonin levels. Leydig cell function was suppressed, evident from reduced smooth endoplasmic reticulum and depletion of testosterone level. Sex accessories function was impaired by showing scanty rough endoplasmic reticulum with depletion of fructose and sialic acid levels. Arecoline treatment that caused pineal dysfunction and testicular stimulation in control rats, suppressed both pineal and testis functions after PTU treatment. The findings suggest that arecoline inhibits pineal–testis function in experimentally induced hypothyroid rats.